The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1183/09031936.05.00136004
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis, HIV seroprevalence and intravenous drug abuse in prisoners

Abstract: High rates of tuberculosis (TB) and HIV are believed to exist in Russian prisons. Prisoners with TB were studied in order to identify the following: 1) prevalence of HIV, and risk factors for HIV and other blood-borne virus infections; and 2) clinical and social factors that might compromise TB treatment effectiveness and/or patient adherence and, hence, encourage treatment failure.A 1-yr cross-sectional prevalence study of 1,345 prisoners with TB was conducted at an in-patient TB facility in Samara, Russian F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 19 publications
(19 reference statements)
7
34
0
4
Order By: Relevance
“…Converging drug-resistant TB and HIV epidemics pose a serious problem and undermine the efforts of national TB control programs (5). There is growing evidence that drug resistance in these settings is strongly associated with the dominating Beijing family of strains (6,10,14,15,17,21,22).…”
mentioning
confidence: 99%
“…Converging drug-resistant TB and HIV epidemics pose a serious problem and undermine the efforts of national TB control programs (5). There is growing evidence that drug resistance in these settings is strongly associated with the dominating Beijing family of strains (6,10,14,15,17,21,22).…”
mentioning
confidence: 99%
“…The Samara Oblast (Central Russia) is a hot spot for both TB and HIV epidemics; ca. 20% of new TB cases are MDR, with rates even higher in previously treated cases and in the prison sector (8). Converging TB, drug-resistant TB, and HIV epidemics pose a serious problem for low-and middle-income countries such as Russia where access to second-and third-line drug therapy is limited (2,8).…”
mentioning
confidence: 99%
“…A survey of several European countries has confirmed that the prevalence of TB in prisons is nearly 100-fold greater than in the general population [28], especially in those subjects with HIV infection [29]. The risk of TB in i.v.…”
Section: Active Case Finding Of Tb In Europe Gh Bothamley Et Almentioning
confidence: 99%